Restauração conservadora na educação: um estudo sobre o projeto das escolas cívico-militares no Brasil - Silva, Thayane Ellen Machado da (2021)
In recent years, Brazilian public education has faced several setbacks due to ideological disputes aimed at serving the interests of the neoconservative agenda through changes instituted mainly by the federal government. This paper will specifically address the National Program of Civic-military Schools, a federal program created in 2019 through Decree No. 10,004/2019, which consists of the militarization of public schools across the country, state and municipal, through the participation of military personnel from the Armed Forces or military police officers and firefighters in school management in the form of a partnership between the Ministry of Education and the Ministry of Defense. The defense for the creation of civic-military schools was the claim of improvement in the quality of education and the increase of scores in large-scale evaluations through an education that prioritizes strict military discipline. However, this militarized school model can be considered a form of conservative updating in education, in the union of neoconservatism and neoliberalism for the interest in transforming the public school into a school that meets the interests of capital. Therefore, in order to understand didactic and pedagogical issues, but also to understand the contextualization of the process of conservative ideology in education, the text was divided to initially understand the historical context of the expansion of militarized thinking in society, to then know the process of creating militarized schools and subsequently analyze the constitutionality and ideology of civic-military schools as a school whose characteristics are very different from a school as stated in the Brazilian Constitution of 1988, the LDB and the ECA. In order to carry out this qualitative research, a bibliographical survey of scientific texts and document analysis was carried out. It was verified at the end of the research that the civicmilitary school is the result of neoconservative interests in instituting a school that meets the needs of the capital, that is, that teaches to obey, emptied of critical content, and that plays the role of propagating conservative ideology in society.